2011
DOI: 10.1161/hypertensionaha.111.175661
|View full text |Cite
|
Sign up to set email alerts
|

Sex Chromosome Complement Contributes to Sex Differences in Bradycardic Baroreflex Response

Abstract: Abstract-To investigate whether sex chromosome complement modulates bradycardic baroreflex response and contributes to the angiotensin II-bradycardic baroreflex sex differences, we used the four core genotype mouse model in which the effect of gonadal sex and sex chromosome complement is dissociated, allowing comparisons of sexually dimorphic traits among XX and XY females, as well as in XX and XY males. In conscious gonadectomized (GDX) MF1 transgenic mice we evaluated baroreflex regulation of heart rate in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
(33 reference statements)
1
20
0
Order By: Relevance
“…One such model — the four core genotype (4CG), in which XY and XX males, and XX and XY females are produced — has clearly shown that both the sex chromosome complement and gender have a role in phenotypic sex-specific differences 89 . For example, the number of X chromosomes can influence adiposity and cardiovascular sexual dimorphisms 90,91 . Using the 4CG mouse model, global gene expression differences that originate from the sex chromosomes have been shown to influence the entire genome, which suggests genome-wide effects 92 .…”
Section: Sex Bias In Gene Expressionmentioning
confidence: 99%
“…One such model — the four core genotype (4CG), in which XY and XX males, and XX and XY females are produced — has clearly shown that both the sex chromosome complement and gender have a role in phenotypic sex-specific differences 89 . For example, the number of X chromosomes can influence adiposity and cardiovascular sexual dimorphisms 90,91 . Using the 4CG mouse model, global gene expression differences that originate from the sex chromosomes have been shown to influence the entire genome, which suggests genome-wide effects 92 .…”
Section: Sex Bias In Gene Expressionmentioning
confidence: 99%
“…Several cardio-metabolic processes have also been shown to be influenced by sex chromosome complement, including stroke sensitivity with aging, cardiac ischemia/reperfusion injury, aortic aneurisms, hypertension, body fluid homeostasis and blood pressure regulation [4853]. Multiple mechanisms could potentially contribute.…”
Section: Potential Mechanisms For the Effects Of X Chromosome Dosamentioning
confidence: 99%
“…In studies of rodents, the sex difference is explained in part by gonadal hormones and partly by sex chromosome complement. Chronic or acute treatment of FCG mice with angiotensin II causes different changes in blood pressure and heart rate in XX vs. XY mice [65,66]. In the FCG model, such XX vs. XY differences are not explained by effects of Sry .…”
Section: Sex Differences In Phenotypes Not Downstream Of Gonadal Diffmentioning
confidence: 99%